2006
DOI: 10.1007/s10549-006-9199-7
|View full text |Cite
|
Sign up to set email alerts
|

LHRH-conjugated Magnetic Iron Oxide Nanoparticles for Detection of Breast Cancer Metastases

Abstract: Targeted delivery of superparamagnetic iron oxide nanoparticles (SPIONs) could facilitate their accumulation in metastatic cancer cells in peripheral tissues, lymph nodes and bones and enhance the sensitivity of magnetic resonance imaging (MRI). The specificities of luteinizing hormone releasing hormone (LHRH) and luteinizing hormone/chorionic gonadotropin (LH/CG)- bound SPIONs were tested in human breast cancer cells in vitro and were found to be dependent on the receptor expression of the target cells, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 63 publications
(96 reference statements)
1
115
0
1
Order By: Relevance
“…The residue was dissolved in distilled water (10 ml) and precipitated by addition of acetone to give GdDOTA (1.34 g, 2.31 mmol, 94%) as a colorless solid. MALDI-MS: m/z calcd for C 16 …”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The residue was dissolved in distilled water (10 ml) and precipitated by addition of acetone to give GdDOTA (1.34 g, 2.31 mmol, 94%) as a colorless solid. MALDI-MS: m/z calcd for C 16 …”
Section: Synthesismentioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the in vivo study showed that the LHRHSPIONs nanoparticle system did not accumulate in the livers of normal mice, suggesting that off-target effects were limited. By contrast, the non-targeted controls accumulated in the liver, making this study one of the best examples of successful selection of specific cancer cells by nanoparticles [52].…”
Section: Breast Cancer Selectionmentioning
confidence: 98%
“…For localised breast cancer selection, another important molecular marker is luteinising hormone-releasing hormone (LHRH) receptor on breast cancer cells. A superparamagnetic iron oxide nanoparticle (SPIONs) based system has been developed for detection of breast cancer metastasis (LHRH-conjugated magnetic iron oxide nanoparticles) [52]. Importantly, the in vivo study showed that the LHRHSPIONs nanoparticle system did not accumulate in the livers of normal mice, suggesting that off-target effects were limited.…”
Section: Breast Cancer Selectionmentioning
confidence: 99%
“…Recently, different types of nanoparticles-based therapeutic and diagnostic agents have been extensively studied to prolong the half-life of drug systemic circulation by reducing immunogenicity, sustained release of drugs in an environmentally responsive manner, lower frequency of administration in order to minimize systemic side effects of drugs for treatment of diabetes [1,2], asthma [3][4][5], allergy [6], infections [7,8], cardiovascular diseases [9], neurological diseases [10], cancers [11,12], pain, and so on. Therefore, a few pioneering therapeutic nanoparticles have been introduced into the pharmaceutical market.…”
Section: Introductionmentioning
confidence: 99%